Effects of multiwalled carbon nanotube, compatibilizers and silane coupling agent on the mechanical and morphological properties of feldspar/polypropylene hybrid composites - Ansari M.N.M.; Atiqah A.; Ismail H. (CRC Press, 2023)
[No abstract available]